Вплив середовища на вибір закладу освіти випускниками шкіл із мовою викладання національних меншин - Горук, Наталія (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The article deals with the issue of school-leavers choice of prospective higher education institutions in the territories of close proximity to borders with the EU. Living in border regions with significant influence of neighboring countries on the development of the mentality and culture of the regions, growing number of migration processes within the European Union, economical instability, and the peculiar features of the microenvironment (family, friends, local communities) are those influential factors that help graduates to build their life strategies and choose future education. Our survey showed that there is a difference in the choice of higher education regarding the language spoken by students at home, higher education of at least one parent, and gender. The nationality declared by the respondents was a factor in the choice of the educational institution: Ukrainians were more likely to indicate the choice of the Ukrainian universities, while students-national minorities were mostly choosing the study abroad. It is argued that school environment, as an important tool for shaping the well-being of future generations, should become a significant aspect in developing students’ consciousness and behavior in order to form certain qualities, beliefs, and spiritual orientations related to civic and national values.
Keywords: graduates; higher education; national minorities; environment